ACCURACY AND UNCERTAINTY OF AIRCRAFT NOISE MODELLING - Zaporozhets, Oleksandr I.; Kartyshev, Oleg O.; Golembievskiy, Gregory G. (Proceedings of National Aviation University (archive), 2008)
Various models for predicting aircraft noise around airports are described. Improved acoustic models of aircraft are formed by summing models for the noise sources peculiar to each of the aircraft types. Their accuracy and uncertainty are assessed by means of comparison with flight trials measurements.